Influence of Environmental Disclosures on the Financial Performance of Public Listed Malaysian Manufacturing Companies - Ong, Tze San; Soh, Wei Ni; Teh, Boon Heng; Ng, Sin Huei (2015)
This study aims to assess the trend of environmental disclosures of publicly listed Malaysian manufacturing companies. It also investigates the relationships among organizational characteristics (control variables), environmental disclosures (independent variables), and financial performance (dependent variables). Based on content analysis our findings involving 120 publicly listed Malaysian companies indicate that most of these companies are cognizant of the importance of environmental disclosures. Results of this study show that environmental disclosures can be divided into pollution abatement and other environmental information. Environmental disclosures are determined to be significantly and positively correlated with financial performance of manufacturing companies.